Heritage Contests: What Can We Learn from Social Movements?. (2nd January 2017) - Jones, Tod; Mozaffari, Ali; Jasper, James M.
ABSTRACT: While contests and conflicts are well recognized in heritage research, analysis of the specific circumstances and dilemmas that individuals and groups face when pursuing heritage goals and partaking in heritage contests can benefit from further methodological work. This paper presents a case and method for incorporating concepts from an emerging interactionist perspective on social movements into heritage research in order to better conceptualize and analyze the interactions and processes through which collective identity and heritage is co-produced. We examine the political and interpretive processes at the heart of heritage research, consider areas in which the language and concepts of social movements addresses existing gaps and disagreements, and identify a set of questions that will open new perspectives on heritage movements and contests. We apply these questions to a heritage contest over the World Heritage site of Pasargadae in Iran, emphasizing how heritage activists advanced their perspectives and claims, eventually leading to the incorporation of Iran's pre-Islamic heritage within the official Islamic republic discourse.